Advancing Health Equity for the Disadvantaged: The Transformative Role of Social Work in Bridging the Gap - Anoop C Choolayil; Dilip G Diwakar (Social Work and Society, 2024)
The constitution of the World Health Organisation (1946) endorses the highest attainable standard of health as a fundamental right. The commitment to the right to health has always been a global priority. The Alma Ata declaration affirmed the global commitment to"the right to health" and the need for all people to attain an acceptable level of health (World Health Organization, 1978) and the Sustainable Development Goals (SDG) target 3.8 emphasises the need to extend accessible and affordable healthcare in the form of Universal Health Coverage (United Nations, 2015). However, despite continued efforts, globally, the violation of the right to health is rampant in the forms of 'violation of commission', 'violation of the obligation to protect', 'failure to fulfil minimum core obligations' and 'violations related to gender discrimination' (Chapman, 1998). The right to health envisioned as health equity is an ambitious goal rooted in the idea of social justice that seeks to attain the highest standard of health possible for all, particularly vulnerable sections of society, as persistent health inequalities can entrap marginalised populations in a vicious cycle of poverty and ill health (Wagstaff, 2002). The social factors that influence and shape health outcomes, commonly known as social determinants of health (SDOH) constitute an important aspect in this regard. SDOH are those conditions"in which people are born, grow, work, live, and age, and the wider set of forces and systems shaping the conditions of daily life," including income, education, occupation, housing conditions and food security, among others, (World Health Organization, n.d.). Addressing SDOH is essential in ensuring the right to health for all, and social work, as a public health profession, advances health equity by addressing the problem of SDOH (Kerson & Lee, 2016).